Logan Medallist 5. Geophysics and Geology: An Essential Combination Illustrated by LITHOPROBE Interpretations-Part 2, Exploration Examples - Clowes, Ron (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2017)
Lithoprobe (1984–2005), Canada's national, collaborative, multidisciplinary, Earth Science research project, investigated the structure and evolution of the Canadian landmass and its margins. It was a highly successful project that redefined the nature of Earth science research in Canada. One of many contributions deriving from the project was the demonstration by example that Earth scientists from geophysics and geology, including all applicable sub-disciplines within these general study areas, must work together to achieve thorough and comprehensive interpretations of all available data sets. In Part 1, this statement was exemplified through studies involving lithospheric structures. In Part 2, it is exemplified by summarizing interpretations from six exploration-related studies derived from journal publications.In the first example, subsurface structures associated with the Guichon Creek batholith in south-central British Columbia, which hosts porphyry copper and molybdenum deposits, are better defined and related to different geological phases of the batholith. Reprocessed seismic reflection data and 2.5-D and 3-D inversions of magnetic and gravity data are combined with detailed geological mapping and drillhole information to generate the revised and improved subsurface interpretation. Research around the Bell Allard volcanogenic massive sulphide deposit in the Matagami region of northern Quebec provides the second example. A seismic reflection line over the deposit shortly after it was discovered by drilling, aided by core and geophysical logs, was acquired to test whether the deposit could be imaged. Direct detection of the ore body from the seismic section would be difficult if its location were not already known; however, structural characteristics that can be tied to lithologies from boreholes and logs were well identified. Nickel deposits and associated structures in the Thompson belt at the western limit of the Superior Province in northern Manitoba were the focus of seismic and electromagnetic (EM) studies combined with geology and physical property measurements. The combined seismic/EM image indicates that the rocks of the prospective Ospwagan Group, which have low resistivity, extend southeastward beneath the Archean gneiss and that structural culminations control the subsurface geometry of the Ospwagan Group.The Sudbury structure in Ontario is famous for its nickel deposits, the largest in the world, which formed as the result of a catastrophic meteorite impact. To help reconcile some of the enigmas and apparent contradictions surrounding studies of the structure and to develop more effective geophysical techniques to locate new deposits, Lithoprobe partnered with industry to carry out geophysical surveys combined with the extensive geological information available. A revised structural model for the Sudbury structure was generated and a 3-D seismic reflection survey identified a nickel deposit, known from drilling results, prior to any mine development. The Athabasca Basin of northwestern Saskatchewan and northeastern Alberta is one of the world's most prolific producers of uranium from its characteristically high-grade unconformity-type deposits and is the only current uranium producer in Canada. An extensive database of geology, drillhole data and physical properties exists. Working with industry collaborators, Lithoprobe demonstrated the value of high-resolution seismic for imaging the unconformity and faults associated with the deposits. The final example involves a unique seismic reflection experiment to image the diamondiferous Snap Lake kimberlite dyke in the Slave Province of the Northwest Territories. The opportunity to study geological samples of the kimberlite dyke and surrounding rocks and to ground-truth the seismic results with drillhole data made available by the two industry collaborators enabled a case history study that was highly successful.